The metabolic syndrome: an overview and proposed mechanisms - Thomaz, Fernanda Santos; John, Oliver Dean; Sinha, Payel; Shafie, Siti Raihanah; Worrall, Simon (Multidisciplinary Digital Publishing Institute, 2024)
Obesity has emerged as a major public health challenge in the 21st century, contributing to the rising prevalence of metabolic syndrome (MetS), a cluster of interrelated health risk factors. These factors include obesity or abdominal obesity, type 2 diabetes mellitus (T2DM), hypertension (HTN), and dyslipidaemia. In this review, we will explore important aspects of metabolic regulation and the dynamics of lipoprotein metabolism to see how they underlie each of these major health risks. Additionally, we will highlight the role of ferroptosis, an iron-dependent regulated cell death process, in relation to inflammatory responses and its critical contribution to the pathophysiology of MetS. These inflammatory responses include inflammasome activation, lipotoxicity, the influence of adipocytokines, and the role of adipose tissue macrophages. By exploring these interconnections, this review aims to provide insights into metabolic crosstalk, outline the pathological mechanisms occurring, and identify potential therapeutic targets for managing and preventing the progression of these health risk factors.